Pre and post-infection microbiome associations with weight gain in pigs co-infected with porcine reproductive and respiratory syndrome virus (PRRSV) and porcine circovirus type 2 (PCV2) - Ober, Rebecca Ariel (Kansas State University, 2018)
Evidence has shown that the gastrointestinal microbiome plays an important role in response to infectious disease. Porcine reproductive and respiratory syndrome virus (PRRSV) and porcine circovirus type 2 (PCV2) are two of the most important pathogens affecting the swine industry worldwide. Co-infections are common on a global scale, resulting in pork production losses through reducing weight gain and causing respiratory disease in growing pigs. Our initial microbiome work demonstrated that the fecal microbiome was associated with clinical outcome of pigs 70 days post-infection (dpi). However, it remained uncertain if microbiome characteristics could predispose response to viral challenge. The purpose of this study was to determine if microbiome characteristics present at the time of viral challenge were associated with outcome after co-infection. Using the Lawrence Livermore Microbial Detection Array, we profiled the microbiome in feces on 0 dpi from pigs identified as having high or low growth rates after co-infection. High growth rate pigs had less severe interstitial pneumonia, reduced PRRSV replication, and a significant increase in average daily weight gain throughout the study. At the level of the fecal microbiome, high growth rate pigs had increased microbial diversity on both a family and species level. Shifts in the microbiome composition of the high growth rate pigs included reduced Methanobacteriaceae species, increased Ruminococcaceae species, and increased Streptococcaceae species when compared to low growth rate pigs. Our results indicate that both microbiome diversity and composition prior to virus exposure may play a role in the subsequent response of pigs to PRRSV/PCV2 co-infection. We followed this study by investigating the microbiome characteristics that are present after co-infection and the role of the microbiome in subclinical infections. Microbiome analysis at 3 and 6 weeks post-infection showed no significant difference between high and low growth rate pigs. The results from both exploring the impact that the initial microbiome has on outcome as well as examining the trends in the microbiome during the post-infection period demonstrate that microbiome pre-infection composition may play a larger role in the outcome of subclinical disease in pigs than microbiome composition during viremia or after viral clearance.
Keywords: PCV2; Microbiome; ProductionPRRS